Pre-service English teachers’ perception of authentic assessment practice in speaking classes - Sukarno Sukarno; Ihtiara Fitrianingsih; Nur Hidayanto Pancoro Setyo Putro; Dwiyani Pratiwi (LITERA, 2023)
There is a growing body of literature examining the significance of authentic assessment in enhancing teachers’ assessment literacy. This study set out to investigate pre-service English teachers’ perception of authentic assessment in their speaking class. This sequential explanatory study employed a set of questionnaires and semi-structured interviews in the data collection. A total of 46 pre-service English teachers in their final year participated in this study. They completed a web-based survey, and four of them who used authentic assessment in their speaking class were selected for an interview. The quantitative data were analyzed using descriptive analysis while the qualitative data were analyzed using thematic analysis. The findings showed that 71.74% of respondents were aware of what authentic evaluation entails as learned from various sources, primarily lecturers and tutors. More than 25% of respondents could not comprehend an authentic assessment, and fewer than a fifth (19.57%) of those surveyed had never taken a course on authentic assessment. The results from the survey and interview also showed that lack of time or the lengthy implementation time of authentic assessment, as well as the class size were reported to be the main challenges of the students in applying authentic assessment. Oral interviews, picture-cued descriptions or stories, information gaps, story/text retelling, role plays/simulations, oral reports, and debates were examples of the authentic assessment tools they normally used. This study implied the need for more authentic assessment trainings and or sessions for these pre-service English teachers in the future.Keywords: perception, authentic assessment, speaking